T CD4+ cells count among patients co-infected with human immunodeficiency virus type 1 (HIV-1) and human T-cell leukemia virus type 1 (HTLV-1): high prevalence of tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM) - Casseb, Jorge; Posada-Vergara, Maria Paulina; Montanheiro, Patrícia; Fukumori, Lígia Maria Ichii; Olah, Ingrid; Smid, Jerusa; Duarte, Alberto José da Silva; Oliveira, Augusto Cesar Penalva de (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
INTRODUCTION: HIV positive patients co-infected with HTLV-1 may have an increase in their T CD4+ cell counts, thus rendering this parameter useless as an AIDS-defining event. OBJECTIVE: To study the effects induced by the co-infection of HIV-1 and HTLV-1 upon CD4+ cells. MATERIAL AND METHODS: Since 1997, our group has been following a cohort of HTLV-1-infected patients, in order to study the interaction of HTLV-1 with HIV and/or with hepatitis C virus (HCV), as well as HTLV-1-only infected asymptomatic carriers and those with tropical spastic paraparesis/HTLV-1 associated myelopathy (TSP/HAM). One hundred and fifty HTLV-1-infected subjects have been referred to our clinic at the Institute of Infectious Diseases "Emílio Ribas", São Paulo. Twenty-seven of them were also infected with HIV-1 and HTLV-1-infection using two ELISAs and confirmed and typed by Western Blot (WB) or polymerase chain reaction (PCR). All subjects were evaluated by two neurologists, blinded to the patient's HTLV status, and the TSP/HAM diagnostic was based on the World Health Organization (WHO) classification. AIDS-defining events were in accordance with the Centers for Disease Control (CDC) classification of 1988. The first T CD4+ cells count available before starting anti-retroviral therapy are shown compared to the HIV-1-infected subjects at the moment of AIDS defining event. RESULTS: A total of 27 HIV-1/HTLV-1 co-infected subjects were identified in this cohort; 15 already had AIDS and 12 remained free of AIDS. The median of T CD4+ cell counts was 189 (98-688) cells/mm³ and 89 (53-196) cells/mm³ for co-infected subjects who had an AIDS-defining event, and HIV-only infected individuals, respectively (p = 0.036). Eight of 27 co-infected subjects (30%) were diagnosed as having a TSP/HAM simile diagnosis, and three of them had opportunistic infections but high T CD4+ cell counts at the time of their AIDS- defining event. DISCUSSION: Our results indicate that higher T CD4+ cells count among HIV-1/HTLV-1-coinfected subjects was found in 12% of the patients who presented an AIDS-defining event. These subjects also showed a TSP/HAM simile picture when it was the first manifestation of disease; this incidence is 20 times higher than that for HTLV-1-only infected subjects in endemic areas.